Research based on tools investigation of security risk assessment according to the information systems resources - Приставка, Филипп Александрович; Павленко, Петр Николаевич; Казмирчук, Светлана Владимировна; Коломиец, Марина Вячеславовна (Ukrainian Information Security Research Journal, 2017)
One of the main stages of integrated systems construction for protecting information resources is risk assessment. Often, specialists of the companies to increase the efficiency of information security pay attention to the choice of adequate tools of information security risks assessment that will meet the relevant requirements. Nowadays there is a wide range of such tools. For their rational choice, a variety of risk assessment tools have been investigated to determine the set of necessary comparative characteristics. According to the mentioned means, taking into account the known analytical-synthetic tuple model of risk characteristics, a tuple is formed, which makes it possible due to the certain parameters, to unify the process of comparative analysis of such means. This will enhance the effectiveness of the choice implementation to solve the corresponding tasks of information security.